A trajetória do trabalho no recôncavo: entre avanços e retrocessos - JESUS, Josias Alves de (2017)
The present research sought to discuss the trajectories because the work in the Recôncavo passed with its advances and setbacks. The Recôncavo was one of the richest regions both from the economic and social point of view of Brazil, but which, throughout its history, has been losing relative importance. The sugar cane industry has helped to produce a complex and multiple society. The production of sugar was mounted on the tripod slavery, land property and export. It generated many riches, but it also generated poverty. In this context, the work has also changed a lot. He went from slave to free and wage-earner. Moved from disqualified to qualified. Thus, research had as general objective to discuss the trajectory of the work in the Recôncavo with its movements of advances and setbacks. These advances and setbacks refer to the cyclical movements because the agricultural crops and the industry in the Recôncavo passed and, consequently, they had bounced on the work. As a research problem, we have: Taking into account the changes that occurred in the various work processes because the Recôncavo has passed since the period of slavery, what are the characteristics of the formal work in the Recôncavo in 2010? The hypotheses that guided the work were: workers in the Recôncavo have low qualification; the salaries paid by companies located in the Recôncavo are low. the social division of labor in the Recôncavo produced differentiated and unequal spaces. The methodology used was the dialectic and history with secondary data of IBGE, PNAD and Censuses. The main conclusions of the research were: the work in the Recôncavo has qualified occupations, like the teachers, but there is still a lot of disqualified work. The salaries paid to workers in the Recôncavo are lower than the national, regional and state average. The territorial division of labor in the Recôncavo produced three distinct spaces (three recôncavo). However, the educational sector stands out in the Recôncavo territory with an increase in the number of employed persons, which can represent a structural improvement of the territory